Endocrine effects of real-life mixtures of persistent organic pollutants (POP) in experimental models and wild fish. Issue 13 (2nd August 2016) - Berg, Vidar; Kraugerud, Marianne; Nourizadeh-Lillabadi, Rasoul; Olsvik, Pål A.; Skåre, Janneche U.; Alestrøm, Peter; Ropstad, Erik; Zimmer, Karin Elisabeth; Lyche, Jan L.
ABSTRACT: A series of studies have assessed the occurrence, levels, and potential adverse effects of persistent organic pollutants (POP) in fish from Lake Mjøsa. In this lake, high levels of various POP were detected in biota. Fish from the nearby Lake Losna contain background levels of POP and served as reference (controls) in these studies. Significantly higher prevalence of mycobacteriosis and pathological changes were documented in burbot ( Lota lota ) from Mjøsa compared to burbot from Losna. Further, transcriptional profiling identified changes in gene expression in burbot from Mjøsa compared to burbot from Losna associated with drug metabolism enzymes and oxidative stress. POP extracted from burbot liver oil from the two lakes was used to expose zebrafish ( Danio rerio ) during two consecutive generations. During both generations, POP mixtures from both lakes increased the rate of mortality, induced earlier onset of puberty, and skewed sex ratio toward males. However, opposite effects on weight gain were found in exposure groups compared to controls during the two generations. Exposure to POP from both lakes was associated with suppression of ovarian follicle development. Analyses of genome-wide transcription profiling identified functional networks of genes associated with weight homeostasis, steroid hormone functions, and insulin signaling. In human cell studies using adrenocortical H295R and primary porcine theca and granulosa cells, exposure to lake extracts from both populations modulated steroid hormone production with significant difference from controls. The results suggest that POP from both lakes may possess the potential to induce endocrine disruption and may adversely affect health in wild fish.